The needs of digital games content rating system in Malaysia - Hamid, Ros Syammimi (2016)
Numerous studies revealed that playing digital games with adverse contents can lead to negative effects. Therefore, this article presents a review of the harmful contents and the detrimental effects of playing digital games.Violent and sexual contents of digital games, digital games scenarios in Malaysia, and review of existing content rating system are covered.The review indicates that Malaysia should have its own digital games content ratings system to control the contents and inform the users about the contents of the games that they wish to consume.